Media Sebagai Agen Ekologi Gerakan Pro-Lingkungan di Era Digital - Meiby Zulfikar; Sarwititi Sarwoprasojo; Dwi Retno Hapsari Hapsari; Aditya Maharani (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The development of new media has opened up great opportunities for increased public participation in environmental issues. Previously, there was still a gap: studies only highlighted the use of social media as a channel for meaningful information, ranging from awareness to collective action, rather than as an agent of ecological change. SOTA indicates a shift from a linear communication model toward a connective action pattern, where individuals collaborate through digital platforms using personalized narratives and citizen data. The study method was descriptive-qualitative systematic literature review. The analysis reviewed the Environmental Communication Matrix theory: Thematic analysis was constructed by integrating the Theory of Planned Behavior, Social Impact Theory, and platform affordances frameworks. The analysis focused on the relationship between new media characteristics, user interaction dynamics, and pro-environmental engagement. The synthesis shows that new media can function as a communication ecosystem, strengthening pro-environmental movements and expanding symbolic participation, such as content sharing, to substantive action. The study emphasizes the need for inclusive communication models, evidence-based content strategies, and cross-actor collaboration to optimize the function of new media as a driver of sustainable environmental action.